Clinical evaluation of the fine impression technique for removable partial dentures - DING Hong; ZHANG Hong; MENG Xiangfeng (口腔疾病防治, 2018)
Objective To provide a clinical reference by evaluating the restorative results of an accurate impression technique for distal ⁃ extension removable partial dentures. Methods Forty ⁃ two patients with free ⁃ end dentition defects who visited the Prosthodontic Department of Nanjing Stomatological Hospital, Medical School of Nanjing University, between April 2017 and January 2018 were selected. The final impression was made by an accurate impression technique to fabricate fifty⁃two removable partial dentures with casting frameworks. The restorative result was judged by clinical examination and patient feedback immediately after wearing dentures and at 1 week, 3 months and 6 months. Results All fifty⁃two dentures for forty⁃two patients were seated successfully, with good retention and stability. Complications occurred throughout the 6 ⁃ month follow ⁃ up, including 4 cases of mucous pain, 4 cases of retention force attenuation and 1 case of abutment fracture. There were no periodontics problems. The dentures garnered high patient satisfaction. Conclusion The accurate impression technique for distal ⁃ extension removable partial dentures showed good clinical results in this follow⁃up investigation.